RECENT TRENDS IN THE CHEMISTRY OF PRIVILEGED SCAFFOLD: 1,4-BENZODIAZEPINE - NAVJEET KAUR, (International Journal of Pharma and Bio Sciences, 2013)
Intention in this review is to present a picture of 1,4-benzodiazepine with particular attention to their reactions and uses in synthetic organic chemistry. Some of these reactions have been applied successfully to the synthesis of biologically important compounds. The main purpose of this review is to present a survey of the literature on 1,4-benzodiazepine chemistry.